Triple therapy (aspirin, clopidogrel and oral anticoagulant) after percutaneous coronary intervention: another call for personalized medicine - (:unkn) unknown (TURKISH SOC CARDIOLOGY, 2013)
Studies indicate that 5-7% patients undergoing percutaneous coronary intervention (PCI) have an indication for anticoagulation therapy. Most commonly atrial fibrillation (AF) is the indication. These subjects require triple therapy with aspirin, clopidogrel, and an oral anticoagulant (OAC). Several questions, concerns and challenges exist regarding the duration, benefit, risks and alternatives related to triple therapy. These questions constitute a moving target with recently approved antiplatelet and anticoagulant agents. This brief review will summarize the current literature regarding triple therapy, potential solutions that can mitigate the formidable risk of bleeding. Arising from that discussion, a logical consensus can be developed that should be applicable to studies with novel agents that interfere with homeostasis. The ultimate goal is to enhance cardiovascular outcome and decrease thrombotic and bleeding complications.
Keywords: Triple therapy; dual antiplatelet therapy; percutaneous coronary stenting; atrial fibrillation; bleeding complications; ASSOCIATION TASK-FORCE; ELEVATION MYOCARDIAL-INFARCTION; DUAL ANTIPLATELET THERAPY; ACCF/AHA FOCUSED UPDATE; ATRIAL-FIBRILLATION; ANTITHROMBOTIC THERAPY; STENT THROMBOSIS; ELUTING STENT; BLEEDING COMPLICATIONS; PREDICTING STROKE